Effect of Pediatric Antibiotics on the Superficial Microhardness of Dental Enamel in Bovine Teeth - Anadely Aída Huaynate Villalobos; Karina Huamán-Mujica; Alberth David Correa Medina (Editorial Ciencias Médicas, 2023)
Objective: To compare the effect of pediatric antibiotics on the superficial microhardness of dental enamel in bovine teeth. Methods: An in vitro study was carried out on 60 non carious bovine teeth. Fifteen teeth were immersed in each group of four solutions (amoxicillin, amoxicillin + clavulanic acid, erythromycin and artificial saliva) for 1 minute three times a day for 7 and 14 days. Enamel surface microhardness was measured at baseline, 7 and 14 days of antibiotic exposure. Results: The enamel surface microhardness of the teeth of the pediatric antibiotic groups was reduced after seven and 14 days of exposure with significant difference (p < 0.001), with respect to the initial microhardness. In addition, in the group exposed to artificial saliva there was no significant difference (p = 0.097) at the different evaluation times. Conclusions: It is concluded that pediatric antibiotics affect enamel microhardness and erythromycin generated the greatest decrease at 14 days of exposure.